Pengaruh Social Capital, Human Capital Dan Financial Technology Terhadap Kinerja Umkm Kuliner Di Kecamatan Padang Timur Kota Padang - Vivi Suci Qamsiani MR; Yulhendri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
Culinary MSMEs in East Padang District are growing rapidly; however, not all businesses are able to optimize their performance. Issues such as unstable revenue, limited human resource quality, and the suboptimal use of financial technology remain key challenges. This study aims to analyze the effects of social capital, human capital, and financial technology on the performance of culinary MSMEs in East Padang District, Padang City. This research employs a quantitative approach with a causal design. The sample consists of 324 respondents selected purposively from a population of 1,689 culinary MSMEs. Data were collected using a Likert-scale questionnaire that has been tested for validity and reliability, and analyzed using SEM-PLS 4.0. The results indicate that social capital has a positive and significant effect on MSME performance (β = 0.120; t = 2.038; p = 0.042), and financial technology also has a positive and significant effect (β = 0.818; t = 9.062; p = 0.000). Meanwhile, human capital does not have a significant effect on MSME performance (β = 0.012; t = 0.142; p = 0.887). Simultaneously, all variables significantly influence MSME performance with an R-square value of 0.865, indicating that 86.5% of the variance in MSME performance is explained by the model.